Kajian Kriminologis Tindak Pidana Pencabulan terhadap Anak di Wilayah Hukum Polresta Denpasar - Ida Bagus Gede Subawa; Putu Sekarwangi Saraswati (Fakultas Hukum, Universitas Warmadewa, 2021)
A crime or a criminal act is a problem that affect humans from time to time, why the commission of a crime can be happening and what pemberantasnya is a problem that little disputed, one of which is of sexual crimes against children. There are several factors of sexual crimes against children the progress in technology that is not only give positive impact but is also negative. Based on the discussion it can problems: is as follows, aims to review the penyabab the pencabulan crimes against children and prevention efforts made by Polresta Denpasar. The research is empirical legal research, empirical research law pull yourself out of the gap between the theory and reality. The method used that is kriminologis approach , approach case , and approach facts. The cause of the factors of sexual crimes against children in the jurisdiction of polresta denpasar caused by internal and external factors. The internal factor caused by existence of in all the world inside of an offender, while the external factor because lack of attention from the parents against children, economic factors, environmental factor, technology factors, factors of alcoholic beverages. The effort to reduce of sexual crimes against children in the jurisdiction of Polresta Denpasar carried out through .